2017
DOI: 10.1002/elps.201700054
|View full text |Cite
|
Sign up to set email alerts
|

Integrated electrokinetically driven microfluidic devices with pH‐mediated solid‐phase extraction coupled to microchip electrophoresis for preterm birth biomarkers

Abstract: Integration in microfluidics is important for achieving automation. Sample preconcentration integrated with separation in a microfluidic setup can have a substantial impact on rapid analysis of low-abundance disease biomarkers. Here, we have developed a microfluidic device that uses pH-mediated solid phase extraction (SPE) for the enrichment and elution of preterm birth (PTB) biomarkers. Furthermore, this SPE module was integrated with microchip electrophoresis for combined enrichment and separation of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 64 publications
(82 reference statements)
0
20
0
Order By: Relevance
“…This flow was contrary to the expected direction of migration and was also observed by Sonker et al. , who photografted the COC surface with PEGDA to yield more reproducible EOF. We used a similar photografting method to that of Sonker et al.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…This flow was contrary to the expected direction of migration and was also observed by Sonker et al. , who photografted the COC surface with PEGDA to yield more reproducible EOF. We used a similar photografting method to that of Sonker et al.…”
Section: Resultsmentioning
confidence: 52%
“…Importantly, by using on‐chip sample preparation steps prior to separation of the biomarkers, we should be able to detect these PTB biomarkers below their risk levels. Using immunoaffinity extraction from blood serum and SPE as described previously, we should be able to achieve sixfold and 50‐fold preconcentrations, respectively, for a combined 300‐fold enrichment of the biomarkers. These enrichment factors should lower the biomarker LODs to near or below the risk level concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a real sample matrix was not tested, this work lays a foundation for the development of pneumatically operated integrated microfluidic systems for biomarker analysis, potentially integrating additional sample preparation steps like analyte labeling. Very recently, Sonker et al [47] reported an integrated SPE device for electrokinetic preconcentration of preterm birth biomarkers. A reversed-phase monolith inside a COC microchannel was used to perform pH-based SPE of clinically relevant low nanomolar concentrations of preterm birth biomarkers with 50-fold sample preconcentration.…”
Section: On-chip Sample Preparation Methodsmentioning
confidence: 99%